KONSTRUKSI CITRA PEREMPUAN DALAM “IKLAN BELVITA BISCUIT VERSI BUNGA CITRA LESTARI” - Wahyu Permana, Fauzia Putri; Sugiarica Joni, I Dewa Ayu; Pascarani, Ni Nyoman Dewi (E-Jurnal Medium, 2018)
ABSTRA C T   Ads can be defined as a form of activity in communicate, attract attention and persuade some or all of the community to take action in responding to the ideas, goods, or services presented. Variety of ways conducted by advertisers in order to get the attention of prospective customers, one of them by using the object. The woman in the ad is always shown as a figure not far from domestic roles, sometimes also positioned as subordinate to men. But in the further development of various stereotypes of women who are weak are now starting to show changes in positions where women are shown at par with men as in ad Belvita Biscuit Bunga Citra Lestari version Image Sustainably. By using descriptive qualitative approach as well as methods of analysis of semiotics Roland Barthes the results of this research show that the construction of the image of women that is formed is a woman who has a position of equality with male or gender equality. Keywords: Advertisement, Constructive, Image, Semiotics, Women